Nutrient metabolism, mass balance, and microbial structure community in a novel denitrifying phosphorus removal system based on the utilizing rules of acetate and propionate - Zhang, Miao; Zhu, Chenjie; Pan, Ting; Fan, Yajun; Soares, Ana; Wu, Jun; He, Chengda (Elsevier, 2020)
The effect of acetate (HAc) and propionate (HPr) on denitrifying phosphorus removal (DPR) was evaluated in a novel two-sludge A2/O - MBBR (anaerobic/anoxic/oxic - moving bed biofilm reactor) system. Results showed that it was the carbon source transformation and utilization especially the composition of poly-β-hydroxyalkanoates (PHA) (mainly poly-β-hydroxybutyrate (PHB) and poly-bhydroxyvalerate (PHV)) decided DPR performance, where the co-exist of HAc and HPr promoted the optimal nitrogen (85.77%) and phosphorus (91.37%) removals. It facilitated the balance of PHB and PHV and removing 1 mg NO3− (PO43−) consumed 3.04–4.25 (6.84–9.82) mgPHA, where approximately 40–45% carbon source was saved. Mass balance revealed the main metabolic pathways of carbon (MAn,C (consumed amount in anaerobic stage) and MA-O,C (consumed amount in anoxic and oxic stages): 66.38–76.19%), nitrogen (MDPR,N (consumed amount in DPR): 57.01–65.75%), and phosphorus (MWS,P (discharged amount in waste sludge): 81.05–85.82%). Furthermore, the relative abundance and microbial distribution were assessed to elucidate DPR mechanism (e.g. Accumulibacter, Acinetobacter, Dechloromonas, Competibacter, and Defluviicoccus) in the A2/O reactor and nitrification performance (e.g. Nitrosomonas, Nitrosomonadaceae and Nitrospira) in the MBBR. Carbon source was demonstrated as the key point to stimulate the biodiversity and bioactivity related to DPR potential, and the operational strategy of carbon source addition was proposed based on the utilizing rules of HAc and HPr.
Keywords: Denitrifying phosphorus removal; MBBR; A2/O; Illumina MiSeq sequencing